2015
DOI: 10.1007/s40262-015-0256-4
|View full text |Cite
|
Sign up to set email alerts
|

A Compartmental Analysis for Morphine and Its Metabolites in Young Children After a Single Oral Dose

Abstract: This model provides a foundation on which to further evaluate the use of oral morphine and its safety in young children. Longer follow-up time for morphine oral doses and incorporation of other important covariates, such as phenotype, will add value and will help overcome the limitations of the presented population pharmacokinetic analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…Recently, several morphine PK models were published to describe the concentration-time profiles of morphine and its 2 major metabolites, M3G and M6G, in adult or pediatric patients after oral administration. 27,28 However, the first-pass effect was estimated as part of the systemic clearance of morphine after oral administration. The concentration-time profile after IV administration of M3G and M6G 19,20 provided the possibility to estimate the absolute volume of distribution and clearance for these 2 metabolites.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, several morphine PK models were published to describe the concentration-time profiles of morphine and its 2 major metabolites, M3G and M6G, in adult or pediatric patients after oral administration. 27,28 However, the first-pass effect was estimated as part of the systemic clearance of morphine after oral administration. The concentration-time profile after IV administration of M3G and M6G 19,20 provided the possibility to estimate the absolute volume of distribution and clearance for these 2 metabolites.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the amount of metabolite from the first‐pass metabolism could not be separated out from the total amount of metabolite in the system circulation, which is a combination of metabolite formed from first‐pass metabolism and systematic metabolism. Recently, several morphine PK models were published to describe the concentration‐time profiles of morphine and its 2 major metabolites, M3G and M6G, in adult or pediatric patients after oral administration . However, the first‐pass effect was estimated as part of the systemic clearance of morphine after oral administration.…”
Section: Discussionmentioning
confidence: 99%
“…Single nucleotide polymorphisms have been described for uridine 5′‐diphospho‐glucuronosyltransferase (UGT2B7), the enzyme responsible for glucuronide conjugation of morphine; however, their impact on clearance and serum morphine and metabolite concentrations is still unresolved . Serum morphine‐3‐glucuronide (M3G) and morphine‐6‐glucuronide (M6G) concentrations were measured in this study and are reported elsewhere . Morphine‐6‐glucuronide is an active metabolite but minimally contributes to central nervous opioid effects after analgesic doses of administered morphine , and only contributes to respiratory depression in children with renal failure .…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have described the optimal dosage of morphine. Four studies included only neonates [23][24][25][26] and four studies consisted of data solely based on children [27][28][29][30] (ranging from 10 to 40 μg/kg). The use of morphine, especially in the preterm, is still a matter for debate.…”
Section: Dose Determination Of Common Analgosedative Drugsmentioning
confidence: 99%